TALABALARNING INTERNET TARMOG`IDA AXBOROTLAR BILAN ISHLASHI KO`NIKMALARINI SHAKLLANTIRISHNING PEDAGOGIK JIHATLARI - Xujaniyozova, Z.O. (SCIENCE and SOCIETY, 2017)
The article is about forming of culture of information in the system of continous education, infhience of information to the interests of the state and society, ways of forming information culture of pupils and youth, we of Internet and infheence of information on the man’s psychiatry.
Keywords: information; to inform education; information attack; the virtual world; information means